DETERMINING TRANS JOGJA BUS STOP LOCATIONS USING A COMBINATION OF SPATIAL ANALYSIS AND FUZZY LOGIC - Maulana Yudinugroho; Dessy Apriyanti; Lia Lidyani (Universitas Sebelas Maret (UNS), 2023)
The increase in population from migration coupled with natural growth resulted in a high population density in Yogyakarta City, with a negative impact of traffic congestion due to the number of vehicles that were not proportional to road capacity. One of the efforts to lessen congestion was through efficient public transportation. Trans Jogja can be one of the solutions to this problem. However, despite having up to 90 stops in Yogyakarta City, the existing stop locations are not evenly distributed. Thus, in order to propose appropriate bus stop locations, this study aimed to utilize the weighting and utilization of GIS, based on a number of factors usithe ng fuzzy logic method. The result showed that the weight of eh parameter also influenced locations with a high suitability. Values with a high match were pixel values ranging from 6.824 to 9.49. The location of high suitability was close to the road around the location with a high level of crowds, such as office areas, shopping centers, hotels, educational facilities, and tourism. This study proved that fuzzy logic could be used as a tool in spatial analysis to obtain criteria for a location by considering the probability of correctness of each selected parameter.